The great emptiness at the beginning of the Universe - Wetterich, Christof (Arxiv, 2019)
We propose the great emptiness as a possible beginning of the Universe in the infinite past of physical time. In the beginning particles are very rare and effectively massless. Only expectation values of fields and average fluctuations characterize the lightlike vacuum of this empty Universe. Our observed inhomogeneous Universe can be extrapolated backwards to the lightlike vacuum in the infinite past, and therefore can have lasted eternally. There is no physical big bang singularity. Standard inflation models admit a primordial flat frame for which spacetime is flat in the infinite past.
Gesehen am 18.02.2020